1996
DOI: 10.1128/mcb.16.4.1401
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of IκBα in the C-Terminal PEST Domain by Casein Kinase II Affects Intrinsic Protein Stability

Abstract: The NF-B/Rel transcription factors participate in the activation of immune system regulatory genes and viral early genes including the human immunodeficiency virus type 1 long terminal repeat. NF-B/Rel proteins are coupled to inhibitory molecules, collectively termed IB, which are responsible for cytoplasmic retention of NF-B. Cell activation leads to the phosphorylation and degradation of IB␣, permitting NF-B/Rel translocation to the nucleus and target gene activation. To further characterize the signaling ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
198
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(202 citation statements)
references
References 65 publications
3
198
1
Order By: Relevance
“…An attractive explanation for this e ect would be that the stabilization of the mutant protein results in increased transactivation potential of mutated c-Myb protein. In fact, PEST sequences rich in proline and serine residues contain many potential sites for protein kinases and phosphorylation dependent degradation of target proteins by the 26S proteasome was already described (Kornitzer et al, 1994;Yaglom et al, 1995;Lin et al, 1996). Interestingly, there is a striking correlation between the increase in half-life of the COOHterminally truncated c-Myb (2.8-fold on average) in this paper and the increase in transactivation activity (2 ± 4 fold) by similarly truncated proteins as reported by others (Sakura et al, 1989Nakagoshi et al, 1992Dini and Lipsick, 1993).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An attractive explanation for this e ect would be that the stabilization of the mutant protein results in increased transactivation potential of mutated c-Myb protein. In fact, PEST sequences rich in proline and serine residues contain many potential sites for protein kinases and phosphorylation dependent degradation of target proteins by the 26S proteasome was already described (Kornitzer et al, 1994;Yaglom et al, 1995;Lin et al, 1996). Interestingly, there is a striking correlation between the increase in half-life of the COOHterminally truncated c-Myb (2.8-fold on average) in this paper and the increase in transactivation activity (2 ± 4 fold) by similarly truncated proteins as reported by others (Sakura et al, 1989Nakagoshi et al, 1992Dini and Lipsick, 1993).…”
Section: Discussionmentioning
confidence: 97%
“…To determine the existence of such sequences in murine cMyb we employed the algorithm PEST-FIND, which scores all sequences of ten or more amino acids residues that are enriched in P, E, S, and T and anked by the basic residues R, K, or H and combines these results with the predicted hydrophilicity of potential PEST sequence (Rogers et al, 1986). In the recent years PEST sequences were linked to the instability signal on many short-lived proteins degraded by the ubiquitin-26S proteasome pathway and their deletion signi®cantly increased stability of several (Kornitzer et al, 1994;Tsurumi et al, 1995;Yaglom et al, 1995;Lin et al, 1996). Our search located three regions in murine c-Myb that had a positive PEST-score (PEST 1, 2 3; see Figure 11a).…”
Section: Discussionmentioning
confidence: 99%
“…The third signaling pathway is classified as atypical because it is independent of IKK, and is activated by UV and doxorubicin, both of which cause DNA damage [105]. UV radiation induces IκBα degradation via the proteasome, but the targeted serine residues are located within a C-terminal cluster, which is recognized by the p38-activated casein kinase 2 [8,68,83]. Oxidative stress also leads to NF-κB activation via IκBα tyrosine phosphorylation [55].…”
Section: Nf-κb Signaling Pathwaysmentioning
confidence: 99%
“…45 Moreover, several reports have shown that phosphorylation may affect intrinsic protein stability as it was described for the IjB inhibitor protein. 29,30,46 Indeed, stimuli such as TNF-a cause rapid phosphorylation of the C-terminal PEST domain of IjB leading to ubiquitinylation and degradation of the inhibitor subunit by the proteasome 26S. NF-jB protein then translocates to the nucleus and activates gene expression.…”
Section: Effect Of Ck2 Inhibition On Hif-1a Stabilitymentioning
confidence: 99%